Legal Review and Impact on Society of Online Gambling in Indonesia - Agus Sugiarto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Online gambling in Indonesia has become a significant topic in the legal and social realms. This research aims to investigate the legal aspects related to online gambling practices and their impact on Indonesian society. The research method used is normative legal analysis to examine various laws, regulations and policies that regulate online gambling in Indonesia. Apart from that, a qualitative approach was also used to understand people's views and experiences regarding online gambling. The research results show that the online gambling phenomenon is a serious problem that affects society at large. Various complex factors such as economic pressure, unemployment, social environment, and lack of effective regulation have been identified as the main triggers for online gambling. Although laws have been passed to prohibit online gambling, implementation and enforcement still face significant challenges. The impact of online gambling on individuals and society includes financial problems, mental health, and social disharmony. Therefore, a holistic approach is needed that involves prevention efforts, economic empowerment, education, and effective law enforcement to overcome this online gambling phenomenon and maintain the welfare of society as a whole. With a deeper understanding of these factors, it is hoped that prevention and law enforcement efforts can be more effective in dealing with the phenomenon of online gambling in society.